Analisis lesi endo-perio di periapikal melalui radiografi - Chrisna Ardhya Medika; Suhardjo Sitam; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2019)
Objectives: Endodontic lesions and periodontal lesions that appear together in the same tooth are called endo-perio lesions. This study is aimed to explain further on radiography characteristics of endo-perio lesions. Case Report: Case 1, A 21-year-old male patient came to RSGM with a lower left lower back pain complaint. The tooth was once cursed 1 year ago. In the radiographic picture there is a large radiolucent lesion on the alveolar bone around the distal root. Case 2, A 25-year-old female patient came to the Installation of Dental Conservation Specialist RSGM FKG Padjadjaran University complained that the lower left molar was sore and swollen gums had been 3 days. The tooth has been treated by a dentist in another city, but the treatment is not completed. Patients have taken the drug of mefenamic acid and amoxicillin each one grain. Conclusion: Periapical radiography is one of diagnostic imaging tools to help establish a more accurate diagnosis of endo-perio lesions.